Pengaruh Audit Tenure, Tingkat Solvabilitas Terhadap Audit Delay Dengan Spesialisasi Auditor Sebagai Vaiabel Pemoderasi - Rosyidi, Ma'ruf; , Drs. Wahyono, Ak, MA (2017)
The study aims to analiyze the influence audit tenure, leverage to the audit delay with specialization auditor as moderating. Kind of this research is quantitative research. The population in this research is mining companies in Indonesia registered in Indonesia Stock Exchange. Determination of sample using purposive sampling and get 17 companies as sample for period 2012-2015. The data collected was secondary data with the methode of documentation. Data analysis technique using Regression Analysis Moderating. The result of this study indicate leverage have a effect on audit delay, while audit tenure and specialization auditor do not have a significant effect on the audit delay.